Necessidades hídricas, desenvolvimento e análise econômica da cultura do milho nas condições do semiárido brasileiro - Santos, Wesley de Oliveira (2014)
The culture of maize (Zea mays L.) has great importance for economic and social order in Brazil, due to its high productivity, nutritional value and the numerous uses in food and feed, fresh and high-tech industry. The cultivation of maize for the production of corn is increased significantly because of profitability, as in the form of green beans, the commercial value is larger as compared to corn in the form of dry grains. The water requirement of maize is variable depending on the prevailing climatic factors during development, variety and stage of culture. If there is one week after water stress anthers arise, there may be a 50% drop in its production, so this study aimed to determine the crop evapotranspiration (ETc) and crop coefficients (Kc) for different stages of development of corn hybrid AG 1051, to evaluate the growth and development and productivity, and economic analysis of corn grown in double rows (1.3 x 0.2 x 0.2 m) under drip irrigation in the community in Alagoinha Mossoró/RN. The measurement was performed daily ETc was used four weighing lysimeters, with an area of 2.25 m2 (dimensions 1.5 x 1.5 m in area and 1 m deep) was performed for monitoring of moisture soil through eight TDR probes (6 merits of Campbell and two built by hand at depths of 0-30 cm and 15-45 cm in the lysimeters installed and planting area. Reference evapotranspiration (ETo) was estimated by method Penman-Monteith-FAO. The crop cycle was 77 days and the total ETo and ETc during this period were 334.90 and 300.54 mm, respectively. Phonological phases were set at 16, 20, 27 and 14 days for initial phase (Phase I), the vegetative development (Phase II) flowering (phase III) and physiological maturation (phase IV), respectively. Crop coefficients obtained for the various stages of development were 0.50, 0.64 , 1.12 and 1.11 for the respective phases I, II, III and IV. Kc values obtained were close to those recommended by the FAO-56 for the corn crop. During the crop cycle, the maximum height of plants were 2.38 m, and the average height corresponding to 1.2 m, the average number of sheets was 14, the average diameter of the crown was 48.28 cm and 81.00 cm maximum corresponding to the plants on single row, double row now for the average diameter of the crown was 98.56 cm and the maximum corresponding to 1.78 m. The average yield for corn (cob with husk) was 12.239 kg ha-1 grain, while for (marketable husked ear) was 6.380 kg ha-1 and grain yield obtained was approximately 5581 kg ha-1. According to the receipts additional/extra cost, it appears that in the case of the practice of harvesting corn ( production system adopted as a reference), each real invested in additional cost, generates $ 59.84 of additional revenue